Bioesai bioinsektisida Beauveria bassiana dari Sumatera Selatan terhadap kutu putih pepaya, Paracoccus marginatus Williams & Granara De Willink (Hemiptera: Pseudococcidae) - Siti Herlinda; Komang Agus Darmawan; Firmansyah Firmansyah; Triani Adam; Chandra Irsan; Rosdah Thalib (Jurnal Entomologi Indonesia, 2012)
In fresh swamp areas of South Sumatra, papaya mealybug, Paracoccus marginatus (Hemiptera: Pseudococcidae) could cause severe damage to young papaya trees and decreased the fruit quality. The objective of this research was to bioassay test of the bioinsecticide Beauveria bassiana againts nymphs of P. marginatus. B. bassiana was conducted on rice medium. The bioinsecticide was formulated using dried compost, compost gram, paddy ash, paddy bran, woody powder, paddy bran mixed with woody powder, compost enriched with Trichoderma virens. Controls used were sterile water (control 1) and isolate of B. bassiana (control 2). Results showed that conidial viability of B. bassiana on control 2 was the highest (46.33%). The viability of control 2 was not significantly different from the formulations with carrier of the paddy bran, the paddy bran mixed with woody powder, and the compost enriched with T. virens. The highest nymph mortality (82.86%) was found on formulation of compost enriched with T. virens and was significantly different from other treatments. The lowest visibly (73.48%) occured on formulation of paddy ash, and was significantly different from other treatments. Mortality on control 1 on average was 29.52%, whereas control 2 averaged of 75.71%. The shortest median lethal time (LT50) (3.55 days) was found on formulation of compost enriched with T. virens but the longest one (3.73 days) occured on the formulation of paddy ash. Overall, the most effective bioinsecticide was the formulation of compost enriched with T. virens.